Hepatic Stellate Cell-Immune Interactions in NASH - Carter, James K.; Friedman, Scott L. (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the dominant cause of liver disease worldwide. NAFLD often advances to nonalcoholic steatohepatitis (NASH), a more aggressive presentation characterized by severe hepatocellular injury, inflammation, and fibrosis. Chronic inflammation and heightened immune cell activity have emerged as hallmark features of NASH and key drivers of fibrosis through the activation of hepatic stellate cells (HSCs). Recent advances in our understanding of the molecular and cellular pathways in NASH have highlighted extensive crosstalk between HSCs and hepatic immune populations that strongly influences disease activity. Here, we review these findings, emphasizing the roles of HSCs in liver immunity and inflammation, key cell-cell interactions, and exciting areas for future investigation.